2022
DOI: 10.3926/jiem.3603
|View full text |Cite
|
Sign up to set email alerts
|

Optimization strategies for the integrated management of perishable supply chains: A literature review

Abstract: Purpose: The main purpose of this article is to systematically review the papers published in the period 2005-2020 about the integration of production, inventory and distribution activities in perishable supply chains.Design/methodology/approach: The proposed research methodology is based on several steps. First, database and keywords are selected, with the aim to search and collect the main papers, dealing with the integration of production, inventory, distribution activities in perishable supply chains. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 108 publications
(223 reference statements)
0
9
0
Order By: Relevance
“…Compared to the literature review on the perishable supply chains, the combination of supplier-to-customer (i.e. from blood bank to TC) is preferred at the second rank in the current study, while it took the first place in perishable supply chains (Mirabelli and Solina, 2022). Looking at the parties involved in the supply chain in the BSC network model, only a few studies that included all parties are found.…”
Section: Blood Supply Chain Network Designmentioning
confidence: 94%
“…Compared to the literature review on the perishable supply chains, the combination of supplier-to-customer (i.e. from blood bank to TC) is preferred at the second rank in the current study, while it took the first place in perishable supply chains (Mirabelli and Solina, 2022). Looking at the parties involved in the supply chain in the BSC network model, only a few studies that included all parties are found.…”
Section: Blood Supply Chain Network Designmentioning
confidence: 94%
“…ZigBee and WSN wireless sensor networks are applied to the cold chain coordination real-time monitoring system to achieve multipoint data collection in cold chain carriages [ 10 ]. For the real-time function of synchronous temperature monitoring, the application of RFID technology to outlier detection is discussed.…”
Section: Related Workmentioning
confidence: 99%
“…The entire flow in the supply chain, from the procurement of raw materials to the delivery of goods to final consumers, is included in the scope of logistics optimization. In the study aimed at systematically reviewing published papers on optimization strategies integrating production, inventory, and distribution (Mirabelli & Solina, 2022), the authors emphasize more on the potential of and warehousing improvements. The study is purely using qualitative methods for analysis.…”
Section: Scl Optimization Techniquesmentioning
confidence: 99%